“Análisis de la aplicación de conocimientos ancestrales en el manejo del cultivo de papa (Solanum tuberosum), en la Comunidad de Jesús del Gran Poder, Parroquia La Libertad, Cantón Espejo, Provincia del Carchi, 2019” - Manosalvas Chafuelán, Luis Armando (2019)
SUMMARY In the research called “Analysis of the application of ancestral knowledge in the management of potato cultivation (Solanum tuberosum), in the Community of Jesus of the Great Power, Parroquia La Libertad, Cantón Espejo, Province of Carchi”, which presents a Introduction where the details of the research to be carried out are found and the following specific objectives are raised: 1) Obtain reasonable and truthful information about the application of ancestral knowledge in potato cultivation (Solanum tuberosum). 2) Make a comparison between conventional agriculture versus ancestral agriculture and its vision. Then we present a theoretical framework where the main concepts to be discussed during the development of the work are exposed, followed by placing our research geographically and exposing the methodology that will be applied for the treatment of the information, it is also described how the results were obtained and they are presented with their respective analysis and finally the conclusions are produced as a result of all the research carried out together with a list of interrelated recommendations. Keywords: potato, ancestral, knowledge, moon, technology.